The Comparison of Expressed Candidate Secreted Proteins from Two Arbuscular Mycorrhizal Fungi Unravels Common and Specific Molecular Tools to Invade Different Host Plants - Kamel, Laurent; Tang, Nianwu; Malbreil, Mathilde; San Clemente, Hélène; Le Marquer, Morgane; Roux, Christophe; Frei dit Frey, Nicolas (Frontiers in Plant Science, 2017)
Arbuscular mycorrhizal fungi (AMF), belonging to the fungal phylum Glomeromycota, form mutualistic symbioses with roots of almost 80% of land plants. The release of genomic data from the ubiquitous AMF Rhizophagus irregularis revealed that this species possesses a large set of putative secreted proteins (RiSPs) that could be of major importance for establishing the symbiosis. In the present study, we aimed to identify SPs involved in the establishment of AM symbiosis based on comparative gene expression analyses. We first curated the secretome of the R. irregularis DAOM 197198 strain based on two available genomic assemblies. Then we analysed the expression patterns of the putative RiSPs obtained from the fungus in symbiotic association with three phylogenetically distant host plants – a monocot, a dicot and a liverwort - in comparison with non symbiotic stages. We found that 33 out of 84 RiSPs induced in planta were commonly up-regulated in these three hosts. Most of these common RiSPs are small proteins of unknown function that may represent putative host non-specific effector proteins. We further investigated the expressed secretome of Gigaspora rosea, an AM fungal species phylogenetically distant from R. irregularis. G. rosea also presents original symbiotic features, a narrower host spectrum and a restrictive geographic distribution compared to R. irregularis. Interestingly, when analysing up-regulated G. rosea SPs (GrSPs) in different hosts, a higher ratio of host-specific GrSPs was found compared to RiSPs. Such difference of expression patterns may mirror the restrained host spectrum of G. rosea compared to R. irregularis. Finally, we identified a set of conserved SPs, commonly up-regulated by both fungi in all hosts tested, that could correspond to common keys of AMF to colonize host plants. Our data thus highlight the specificities of two distant AM fungi and help in understanding their conserved and specific strategies to invade different hosts.